Diffusion influence on the speed of pulsating travelling fronts in KPP-Type problems - Valdez, Adrian Roy L. (Department of Mathematics, College of Science, University of the Philippines Diliman, 2007)
Front propagation is a phenomenon which occur in many scientific areas such as chemical kinesis, combustion, biological invasion and population dynamics, transport in porous media, and industrial deposition process.